Dynamics of archaeal community in soil with application of composted tannery sludge - Miranda, Ana Roberta Lima; Mendes, Lucas William; Lemos, Leandro Nascimento; Antunes, Jadson Emanuel Lopes; Amorim, Marineide Rodrigues; Melo, Vania Maria Maciel; de Melo, Wanderley Jose [UNESP]; Van den Brink, Paul J.; Araujo, Ademir Sergio Ferreira (Springer Nature, 2019)
Application of composted tannery sludge (CTS) could promote a shift in the structure of soil microbial communities. Although the effect of CTS on bacterial community has been studied, it is unclear how the composition and diversity of archaeal community respond to CTS amendment and which environmental factors drive the community over time. Here, we hypothesize that the Archaea structure and composition respond to CTS amendment over the time. CTS had been previously applied annually along 6 years and this assessment occurred for 180 days following the application in the 7 th year by using different rates (0, 2.5, 5, 10 and 20 ton ha −1 ). We used amplicon 16S rRNA sequencing to assess the changes in the structure of the archaeal community. Thaumarchaeota and Euryarchaeota were the most abundant phyla found in soils with application of CTS, with Thaumarchaeota dominating the sequences in all samples with relative abundances of >98%. We observed a decreasing trend on the archaeal diversity over the time with increasing CTS application rate, together with an increase in the community similarity. The redundancy analyses (RDA) explained 43% of the total variation in operational taxonomic units and identified Na, pH, Cr and P as the main drivers of the archaeal community over time after application of highest CTS rates. CTS application changes the structure of Archaea community, with significant increase of Thaumarchaeota and Aenigmarchaeota groups, which can be further explored for its biotechnological use in contaminated soils.